Hierarchical metal exposure in umbilical cord blood in relation to oxidative stress and AMPK/NF-κB signaling in preterm membrane rupture - Siqi Lu; Yikun Zhao; Weibing Chen; Yingying Niu; Dapeng Wang; Zhenai Jin (Scientific Reports)
Abstract To investigate the correlation between metal element levels, AMPK(AMP-activated protein kinase) and NF-κBp65(Nuclear factor kappa-B p65) and PPROM(preterm premature rupture of membranes). 20cases of PPROM,33cases of TPROM(Term premature rupture of membranes), and 33cases of nPROM were selected, totaling 86patients.Metal element content in umbilical cord blood serum was measured using ICP-MS(Inductively Coupled Plasma Mass Spectrometry).HE(Hematoxylin-eosin) staining was utilized to observe histological changes in the placentas of the three groups.IHC(Immunohistochemistry) and Western Blot were applied to detect the expression levels of AMPKα and NF-κBp65 in the placental tissues. The levels of Mg, Fe, and Mo in the PPROM group were significantly lower than those in the nPROM group and TPROM group(P<0.05).The levels of Al, Cr, and As in the PPROM group were significantly higher than those of the TPROM group(P<0.05).The incidence of chorioamnionitis in the PPROM group was higher than that in the TPROM group and nPROM group(P < 0.05).The positive expression rates of AMPKα and NF-κBp65 in the placental tissues of the PPROM group were lower than those of the TPROM group and the nPROM group(P < 0.05). Exposure to Al, Cr, As during pregnancy or a deficiency in Mg, Fe, Mo may be among the risk factors for PPROM.The decreased expression of AMPK and NF-κBp65 in placental tissue may be one of the mechanisms contributing to the occurrence of PPROM.